Method for improving corrosion resistance of martensitic steel through protection-layer-free laser shock peening combined grinding
By slightly polishing and pulse laser treatment on the surface of martensite steel after unprotected laser impact strengthening, the problem of degraded corrosion resistance is solved, and surface gloss recovery and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411671085.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
After laser impact strengthening without protective layer, the corrosion resistance of martensite steel decreases, mainly due to surface ablation and high residual tensile stress.
After the laser impact strengthening without protective layer, light polishing is performed to remove the black ablation layer, restore the surface gloss, and promote grain refinement and carbide decomposition through mechanical effects caused by pulsed laser to form a surface passivation film rich in Cr2O3.
Effectively remove ablation layers, improve the corrosion resistance of martensite steel, and ensure improvement and improvement of surface performance.
Smart Images

Figure CN119506559A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy surface modification, and in particular relates to a method for improving the corrosion resistance of martensitic steel by laser shock strengthening combined with grinding without a protective layer. Background Art
[0002] Laser shock peening is an advanced surface treatment technology that mainly uses high-energy laser to irradiate the surface of the material, induce the formation of plasma, and then generate shock waves, which trigger plastic deformation of the material surface and remodeling of the microstructure. In the traditional laser shock peening process, a protective layer (such as black paint, black tape or aluminum foil, etc.) is usually applied to the surface of the workpiece. This strategy aims to protect the workpiece from the thermal effects caused by laser ablation. The function of the protective layer is to absorb high-energy laser pulses, quickly melt and vaporize, and generate high-temperature and high-pressure plasma. Under the constraint of a confinement layer (such as water or optical glass), the plasma propagates into the material, forming shock waves, inducing surface plastic deformation, and finally forming a stable compressive residual stress layer on the surface of the material, refining the grains, and improving the fatigue life and corrosion resistance of the material. However, in the actual production and processing process, when the laser energy used in laser shock peening is high, the protective layer on the surface of the processed material is easily damaged, the processing quality cannot be guaranteed, and the product yield is reduced.
[0003] Compared with traditional laser shock peening, the laser shock peening technology without a protective layer directly allows the laser to act on the surface of the material, and generates shock waves through the direct interaction between the laser and the surface of the material. The effect of the heat load on the surface of the material in this process on its corrosion resistance varies from material to material. Taking steel as an example, laser shock peening without a protective layer may cause laser ablation, causing surface melting and severe surface coarsening, increasing surface roughness and generating high residual tensile stress. The rough surface may expand the area of corrosion, which may increase the corrosion rate; high residual tensile stress cannot effectively inhibit the invasion of corrosive elements into the surface, thereby further reducing the corrosion resistance of the material. In addition, during the laser shock peening process without a protective layer, more hydroxides will be produced by the interaction between the laser beam, the surface of martensitic stainless steel and the flowing water, and the Cr element in the matrix will combine with the oxygen element to form Cr8O 21 Oxidized particles lead to a decrease in the ratio of the formed Cr2O3 passivation film to chromium hydroxide, which will eventually lead to a decrease in the corrosion resistance of martensitic steel. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a method for improving the corrosion resistance of martensitic steel by laser shock strengthening without a protective layer and grinding. The corrosion resistance of martensitic steel after laser shock strengthening without a protective layer will decrease, which is mainly due to surface ablation. The present invention can effectively remove the black ablation layer through subsequent grinding treatment, restore the original surface gloss of martensitic steel, and improve the corrosion resistance of martensitic steel, ensuring the improvement and enhancement of the surface performance of martensitic steel.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for improving the corrosion resistance of martensitic steel by laser shock strengthening combined with grinding without a protective layer comprises the following steps:
[0007] Grinding pretreatment of martensitic steel;
[0008] The pretreated martensitic steel is subjected to a non-protective layer laser shock peening treatment, and during the non-protective layer laser shock peening treatment, running water is sprayed on the surface of the martensitic steel throughout the process;
[0009] The martensitic steel after laser shock peening without protective layer is ground until the black ablation layer is completely removed.
[0010] In the process of laser shock strengthening without protective layer, the ultrashort pulse laser directly acts on the surface of martensitic steel, and cooperates with the constraining layer such as water or optical glass to induce violent physical and chemical reactions on the surface of martensitic steel. Due to the lack of protection of traditional protective layer, the laser directly ablates the surface of martensitic steel, resulting in a large amount of Cr8O 21 The formation of oxidized particles causes surface coarsening and induces residual tensile stress, resulting in a significant decrease in corrosion resistance. In order to alleviate this problem, the present invention slightly polishes the surface of martensitic steel after laser shock strengthening without a protective layer to remove the black ablation layer caused by laser ablation. This step can restore the surface finish of the martensitic steel and form a bright array pit surface. After removing the black ablation, the mechanical effect caused by the pulsed laser causes the martensite to undergo grain refinement while promoting the local decomposition of chromium-containing carbides, forming a surface passivation film rich in Cr2O3, which significantly improves the corrosion resistance of the martensitic steel.
[0011] Preferably, the step of the polishing pretreatment is: firstly polishing the surface of the martensitic steel to be processed with sandpaper, and then performing ultrasonic cleaning with anhydrous ethanol.
[0012] Preferably, the step of first grinding the surface of the martensitic steel to be processed with sandpaper is: using 180-1500# SiC sandpaper to grind the surface of the martensitic steel to be processed step by step.
[0013] Preferably, the ultrasonic cleaning time using anhydrous ethanol is 12-18 minutes.
[0014] More preferably, the ultrasonic cleaning time using anhydrous ethanol is 15 minutes.
[0015] More preferably, the step of pre-treating the martensitic steel by grinding is as follows: the surface of the martensitic steel to be processed is grinded step by step with #180, #400, #800, #1200 and #1500 sandpaper in sequence, and finally ultrasonically cleaned with anhydrous ethanol for 15 minutes. Pre-treating martensitic steel by grinding has at least the following effects: (1) Improving the surface state: Pre-treating by grinding can remove defects such as scale, rust, burrs, etc. on the surface of martensitic steel, providing a clean and uniform surface for subsequent processing; (2) Promoting uniform heat treatment: Pre-treating by grinding can reduce the stress on the surface and inside of the material, and prevent cracks and deformation during the subsequent laser shock strengthening treatment without a protective layer, thereby obtaining a more uniform structure and performance; (3) Improving corrosion resistance: For martensitic stainless steel, the surface state has an important influence on its corrosion resistance, and grinding can improve the corrosion resistance of the martensitic steel. Pretreatment can remove the chromium-depleted layer on the surface, restore and improve the corrosion resistance of the material; (4) Optimize the microstructure: By controlling the degree of grinding, the amount of residual + reversed austenite after the final unprotected layer laser shock strengthening treatment can be affected, thereby affecting the strength and toughness of the material; (5) Improve processing quality: Grinding pretreatment can improve the surface roughness of martensitic steel, reduce friction and wear during processing, and improve the dimensional accuracy and surface quality of the processed parts; (6) Enhance welding performance: Grinding pretreatment can remove surface impurities and reduce welding defects such as pores and cracks.
[0016] Preferably, when the unprotected layer laser shock peening treatment is performed, the spot energy is 3-15J, the spot diameter is 1-6mm, the spot overlap rate is 30-70%, the spot pulse width is 16-20ns, the laser wavelength is 1064nm, and the frequency is 2Hz.
[0017] Preferably, when the unprotected layer laser shock peening treatment is performed, the spot energy is 5-15J, the spot diameter is 1-3mm, the spot overlap rate is 30-60%, the spot pulse width is 16-18ns, the laser wavelength is 1064nm, and the frequency is 2Hz.
[0018] More preferably, when the unprotected layer laser shock peening treatment is performed, the spot energy is 10 J, the spot diameter is 1 mm, the spot overlap rate is 60%, the spot pulse width is 18 ns, the laser wavelength is 1064 nm, and the frequency is 2 Hz.
[0019] The increase of spot energy will lead to an increase in the energy absorbed by the surface area of martensitic steel (referred to as "material"), thereby increasing plastic deformation and dislocation density, resulting in an increase in residual compressive stress in the surface area. Residual compressive stress can improve the corrosion resistance of the material because they can hinder the penetration of corrosive media and the expansion of cracks. Different spot diameters have an effect on the corrosion resistance of laser shock strengthened aluminum alloys. Smaller spot diameters (such as 0.3mm) may have poorer surface morphology than larger spot diameters (such as 3mm), thus affecting its corrosion resistance. This is because smaller spots may produce higher surface roughness, which may increase the risk of local corrosion. The increase in the spot overlap rate can increase the number of laser shocks in the overlap area, thereby increasing the residual compressive stress. Increasing the spot overlap rate within a certain range helps to increase the residual compressive stress, but excessive overlap rates may lead to stress relaxation effects and reduce residual compressive stress, while the increase in residual compressive stress helps to improve the corrosion resistance of the material. The spot pulse width affects the distribution and action time of the laser energy, thereby affecting the plastic deformation and residual stress state on the material surface. Shorter pulse widths (such as nanoseconds) can produce higher strain rates, which help induce grain refinement and carbide fragmentation, thereby improving corrosion resistance. The laser wavelength affects the absorption efficiency of the coating and the formation of plasma, which in turn affects the generation of laser shock waves and the plastic deformation of the material. Different wavelengths may have different effects on the absorption characteristics and heat-affected zones of the material surface, thereby indirectly affecting corrosion resistance. The frequency of the laser affects the energy input per unit area and the size of the heat-affected zone. Higher frequencies may cause more heat accumulation, affecting the microstructure and residual stress state of the material, thereby affecting corrosion resistance. In summary, the various parameters in the laser shock strengthening process act together on martensitic steel to improve its corrosion resistance by affecting the microstructure, residual stress state and surface roughness of the material surface. The present invention can significantly improve the corrosion resistance of martensitic steel by optimizing these parameters.
[0020] Preferably, the step of grinding the martensitic steel after laser shock strengthening without a protective layer is: grinding the black ablation layer with a scouring pad and abrasive paste in sequence until the black ablation layer is completely removed.
[0021] Preferably, the scouring pad is a 7447C scouring pad, and the abrasive paste is one of W2.5-W28 diamond abrasive pastes.
[0022] Scouring pads are superior to other non-woven products such as steel wool, wire brushes or sandpaper in cleaning or finishing. It contains extremely fine aluminum oxide abrasives and can be used for cleaning, surface treatment, abrasive grains, and removal of convex edges and lint without the need for additional cleaning of the work surface. The scouring pad can be folded, stacked or rolled up for effective cleaning or conditioning on flat, irregular or wavy surfaces. The performance of the 7447C scouring pad is comparable to that of grade 1 steel wool, but it will not tear during use, will not rust after use, and will not produce fine metal fragments. The finish of martensitic steel processed with diamond abrasive paste can reach a very high level, which is convenient for the subsequent application of martensitic steel. The present invention uses a scouring pad to remove the ablation layer, and the internal strengthening layer will not be removed (reflected in the bright surface with bumps after polishing), ensuring the improvement and enhancement of the surface performance of the martensitic steel.
[0023] Compared with the prior art, the present invention has the following advantages and technical effects:
[0024] 1. Considering the risk of damage to the protective layer during laser shock peening with a protective layer, which in turn affects the surface processing quality, the present invention can effectively reduce the defective rate in the processing process by combining the laser shock peening technology without a protective layer with a slight grinding process.
[0025] 2. The corrosion resistance of martensitic steel samples after laser shock strengthening without a protective layer may decrease, which is mainly due to surface ablation. After laser shock strengthening without a protective layer on martensitic steel, the present invention can effectively remove the black ablation layer through subsequent grinding treatment, restore the original surface gloss of the martensitic steel, and improve the corrosion resistance of the martensitic steel, ensuring the improvement and enhancement of the surface performance of the martensitic steel.
[0026] 3. The present invention successfully expands the application field of the unprotected layer laser shock strengthening method, enabling it to adapt to more material and process requirements, and enhancing its applicability and flexibility in the industrial field.
[0027] 4. Compared with other complex laser shock peening methods that require precise control of the coating quality of the protective layer, the process operation of the present invention is simpler and more flexible. It eliminates the strict requirements for the quality control of the protective layer coating, and only requires the grinding of the ablation layer when necessary, thereby reducing the dependence on the technical level of the operator, improving the operability and stability of the production process, and bringing higher efficiency and reliability to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0029] Figure 1Comparison of protective layer damage and surface processing quality of martensitic stainless steel after laser shock strengthening with different energies. Other parameters are the same, only the spot energy is different, (a) the spot energy is 4J, (b) the spot energy is 5J, (c) the spot energy is 6J;
[0030] Figure 2 The macroscopic surface morphology (1 mm) of AR (a), AR-G (c), LSPwC (b) and LSPwC-G (d) samples;
[0031] Figure 3 is the surface roughness of AR, AR-G, LSPwC and LSPwC-G;
[0032] Figure 4 is the residual stress of AR, AR-G, LSPwC and LSPwC-G;
[0033] Figure 5 TEM images of the typical low-magnification cross-sectional microstructure of LSPwC, (a) is the typical low-magnification cross-sectional microstructure TEM image of LSPwC, (b) is the electron diffraction image of the selected area in (a), and (c) is the enlarged image (100nm) of the selected area in (a);
[0034] Figure 6 TEM images of the typical cross-sectional microstructure of LSPwC-G. (a) is the TEM image of the typical cross-sectional microstructure of LSPwC-G. (b) is the microstructure of the LSPwC-G sample at a depth of about 3 μm. The scale bar in the inset of (b) is 5 nm.
[0035] Figure 7 Electrochemical impedance spectra of AR, AR-G, LSPwC and LSPwC-G measured in 3.5wt.% sodium chloride solution;
[0036] Figure 8 The electrochemical impedance spectrum of the sample of Example 2 measured in a 3.5wt.% sodium chloride solution;
[0037] Fig. 9 The electrochemical impedance spectrum of the sample of Example 3 measured in a 3.5wt.% sodium chloride solution;
[0038] Fig.10 Cr element XPS fine spectra of AR (a), LSPwC (b) and LSPwC-G (c);
[0039] Fig.11 Schematic diagram of the corrosion mechanism of LSPwC (a) and LSPwC-G (b). DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0046] All raw materials used in the examples of the present invention are commercially available.
[0047] Laser Shock Peening without Coating (LSPwC) is abbreviated as LSPwC process. This technology uses high-frequency, low-energy nanosecond pulse laser to directly irradiate the material surface. It can adapt to special processing environments while ensuring the strengthening effect and improving processing efficiency. In the process of laser shock peening without coating, ultrashort pulse laser directly acts on the surface of martensitic steel, and cooperates with the constraining layer such as water or optical glass to induce violent physical and chemical reactions on the surface of martensitic steel. Due to the lack of protection of traditional protective layer, laser directly ablates the surface of martensitic steel, resulting in a large amount of Cr8O 21 The formation of oxidized particles causes surface coarsening and induces residual tensile stress, resulting in a significant decrease in corrosion resistance. In order to alleviate this problem, the present invention slightly polishes the surface of martensitic steel after laser shock strengthening without a protective layer to remove the black ablation layer caused by laser ablation. This step can restore the surface finish of the martensitic steel and form a bright array pit surface. After removing the black ablation, the mechanical effect caused by the pulsed laser causes the martensite to undergo grain refinement while promoting the local decomposition of chromium-containing carbides, forming a surface passivation film rich in Cr2O3, which significantly improves the corrosion resistance of the martensitic steel.
[0048] Martensitic steel refers to some high-strength steels above 600MPa, such as steel for engineering machinery above 800MPa, steel for pressure vessels and storage tanks above 600MPa, etc. When this type of steel is heated to a high temperature, the structure is austenite, and when cooled to room temperature, it turns into martensite, so it can be strengthened by heat treatment. It is generally used in the quenching-tempering (quenching and tempering) state. The chromium content of martensitic stainless steel is generally in the range of 12%-18% (mass percentage). When the chromium exceeds 15%, it is often necessary to add a certain amount of nickel or appropriately increase the carbon content to balance the structure. In the present invention, the type of martensitic steel is not limited. As long as it is martensitic steel, the method of the present invention can improve its corrosion resistance to a certain extent. In some embodiments of the present invention, 2Cr13 martensitic stainless steel is used as an example.
[0049] In the laser shock peening process without protective layer in the embodiment of the present invention, the "surface to be processed" of martensitic steel refers to the surface area of martensitic steel that needs to be processed before laser shock peening. This surface area will be directly affected by the laser shock wave to achieve the improvement of the surface properties of the material, including but not limited to increasing the surface hardness, introducing residual compressive stress, refining the grain structure, etc.
[0050] In the embodiment of the present invention, the spot energy refers to the energy carried by the laser pulse when it acts on the surface of the material, usually in joules (J). This energy determines the intensity of the interaction between the laser and the material, and further affects the plastic deformation and residual stress generation on the surface of the material.
[0051] In the embodiment of the present invention, the spot diameter refers to the diameter of the spot formed by the laser beam on the surface of the material, which is usually measured in millimeters (mm). The size of the spot diameter directly affects the concentration of laser energy and the coverage of the impact area.
[0052] In the embodiment of the present invention, the spot overlap rate refers to the degree of overlap between two adjacent spots, usually expressed as a percentage. It is defined as η i =1-Si / 2R×100%, where η i is the overlap rate (%), Si is the distance between two adjacent light spots (mm), and R is the radius of the light spot (mm). The overlap rate affects the surface profile, residual stress distribution and fatigue performance of the material.
[0053] In the embodiment of the present invention, the spot pulse width refers to the duration of the laser pulse, which is usually measured in nanoseconds (ns). The pulse width determines the release rate of laser energy and affects the formation of plasma and the generation of shock waves.
[0054] In the embodiments of the present invention, the laser wavelength refers to the distance from the peak to the peak of the laser light wave in one cycle, usually in nanometers (nm). The wavelength affects the interaction between the laser and the material, including reflection, absorption, and the generation of plasma. Lasers of different wavelengths have different reflectivity and absorptivity on the surface of the material, thereby affecting the effect of laser shock strengthening.
[0055] In the embodiment of the present invention, frequency refers to the repetition rate of laser pulses, which is usually measured in Hertz (Hz). The frequency determines the number of laser shocks per unit time and affects the heat accumulation and plastic deformation of the material.
[0056] In the present invention, "light grinding" refers to grinding the black ablation layer formed after the laser shock peening treatment without the protective layer with a scouring pad and abrasive paste until the black ablation layer is completely removed. In some typical embodiments, the actual grinding depth is 3-5 μm.
[0057] In the embodiment of the present invention, W2.5-W28 diamond grinding paste is an industrial material used for grinding and polishing, and its characteristics and applications are as follows:
[0058] 1. Particle size: The particle size of W2.5-W28 diamond grinding paste ranges from 28 microns to 1.5 microns. The specific particle size and model correspondence are as follows:
[0059] W28: 28-20 microns;
[0060] W20: 20-16 microns;
[0061] W16: 16-10 microns;
[0062] W10: 10-7 microns;
[0063] W7: 7-5 microns;
[0064] W5: 5-3 microns;
[0065] W2.5: 2.5~1.5 microns.
[0066] 2. Color marking: Diamond pastes of different particle sizes have different color markings for easy identification and distinction. For example, the color marking of the W28 model is gray; the color marking of the W2.5 model is rust red, and the finish after processing can reach level 12 to 13.
[0067] 3. Smooth finish after processing: The smooth finish after processing with diamond abrasive paste can reach a very high level, ranging from level 9 to level 14, depending on the particle size and application.
[0068] 4. Diamond content: Different types of diamond paste contain different amounts of diamonds, ranging from 1 carat to 1.5 carats. For example, the diamond content of the W28 model is 1.5 carats, and the diamond content of the W2.5 model is 1 carat.
[0069] Comparison of protective layer damage and surface processing quality of martensitic stainless steel after laser shock strengthening with different energies Figure 1 The martensitic stainless steel is 2Cr13 martensitic stainless steel. According to the national standard GB / T 1220-2007, its specific chemical composition is 0.20% C, 0.45% Si, 0.41% Mn, 0.006% S, 0.021% P, 12.61% Cr, 0.53% Ni, 0.12% Cu, and the balance is Fe (weight percentage); the martensitic stainless steel used is first austenitized at 1020°C for 1 hour, then oil quenched to room temperature, and finally tempered at 750°C for 2 hours, and then air-cooled.
[0070] Figure 1 This is a comparison of the damage of the protective layer and the surface processing quality of martensitic stainless steel after laser shock strengthening with different energies. The macroscopic images of the samples were obtained when the "Z" type processing path was adopted for all samples and other parameters except the spot energy were kept the same. Specifically, Figure 1(a) is a macroscopic processing effect diagram of the sample after laser shock peening with 4J spot energy. The black tape protective layer remains intact and there is no ablation mark on the sample surface. After laser shock peening with 5J spot energy, the black tape protective layer is damaged and local ablation occurs on the sample surface. Figure 1 As shown in (b); after laser shock strengthening with 6J spot energy, the black tape protective layer is severely damaged and the ablation marks are aggravated, as shown in Figure 1 As shown in (c), it can be seen that when the laser energy used in laser shock peening is high, the protective layer on the surface of the processed material is easily damaged, the surface of the sample is easily ablated, and the processing quality of the sample cannot be guaranteed.
[0071] The technical solution of the present invention is further illustrated by the following embodiments.
[0072] Example 1
[0073] The surface to be processed of 2Cr13 martensitic stainless steel (referred to as "sample") was polished step by step with #180, #400, #800, #1200 and #1500 sandpaper, and finally ultrasonically cleaned with anhydrous ethanol for 15 minutes, and the pretreated sample was fixed to the processing platform. The laser was used for laser shock strengthening without protective layer, with a laser wavelength of 1064nm, a spot energy of 7.6J, a spot diameter of 3mm, a frequency of 2Hz, a spot overlap rate of 50%, and a spot pulse width of 16ns. The surface processing area of the sample was 10mm×10mm, the processing path was a traditional Z-shaped processing path, and the processing starting point and end point were both the corners of the sample. The water spray robot was used to spray water on the surface of the sample, and the laser strengthening equipment was turned on to complete the laser shock strengthening without protective layer. The strengthened sample was lightly polished 3-5μm with a 7447C scouring pad and W10 diamond grinding paste to completely remove the black ablation layer, which was recorded as LSPwC-G.
[0074] Example 2
[0075] Same as Example 1, except that when performing laser shock peening treatment without a protective layer, the laser wavelength is 1064nm, the spot energy is 10J, the spot diameter is 1mm, the frequency is 2Hz, the spot overlap rate is 60%, and the spot pulse width is 18ns.
[0076] Example 3
[0077] The same as Example 1, except that when performing laser shock peening treatment without a protective layer, the laser wavelength is 1064nm, the spot energy is 5J, the spot diameter is 3mm, the frequency is 2Hz, the spot overlap rate is 40%, and the spot pulse width is 20ns.
[0078] Comparative Example 1: No laser shock peening treatment and no grinding
[0079] The surface to be processed of 2Cr13 martensitic stainless steel was polished in turn with #180, #400, #800, #1200 and #1500 sandpapers, and finally ultrasonically cleaned with anhydrous ethanol for 15 min, which was recorded as AR.
[0080] Comparative Example 2: No laser shock peening treatment but polished
[0081] The surface to be processed of 2Cr13 martensitic stainless steel (referred to as "sample") was polished step by step with #180, #400, #800, #1200 and #1500 sandpapers, and finally ultrasonically cleaned with anhydrous ethanol for 15 minutes, and lightly polished with 7447C scouring pad and W10 diamond grinding paste. The polishing time was the same as in Example 1, recorded as AR-G.
[0082] Comparative Example 3: No protective layer laser shock strengthening followed by polishing
[0083] The same as Example 1, except that no polishing treatment is performed after the laser shock peening without protective layer is completed, which is denoted as LSPwC.
[0084] The performance of each sample was tested, and the samples obtained in Example 1 and Comparative Examples 1 to 3 were used as examples for illustration:
[0085] The macroscopic surface morphology of AR, AR-G, LSPwC and LSPwC-G samples is shown in Figure 2 It can be seen that the LSPwC sample produced an obvious black ablation layer after laser shock strengthening. After using a scouring pad to remove these black ablation layers, the surface of the LSPwC-G sample regained its gloss and had obvious bright array pit surface features. The surface roughness parameter Sa (arithmetic mean) of each sample was measured using a VK-X200 three-dimensional laser micro-morphometer. The results are shown in Figure 3 As shown. After LSPwC treatment, the surface roughness of the samples increased significantly. The Sa value of the AR-treated sample was ~0.028μm, while the Sa value of the LSPwC-treated sample was ~0.681μm. After slight polishing with a scouring pad and abrasive paste, the Sa value of the AR-G sample increased from ~0.028μm to ~0.356μm, while the Sa value of the LSPwC-G sample decreased from ~0.681μm to ~0.305μm, which is comparable to the AR-G sample.
[0086] The residual stress of each sample was measured using an X-350A X-ray stress diffractometer. Figure 4As shown. The surface of the AR sample after sandpaper polishing showed residual compressive stress, with an average value of -298MPa. After further light polishing with scouring pad and abrasive paste, the residual compressive stress on the surface of the AR-G sample increased slightly to -324MPa. In contrast, due to laser ablation, the residual tensile stress of the LSPwC sample is higher (227MPa). However, the residual compressive stress value of the LSPwC-G sample after light polishing with scouring pad and abrasive paste is the largest, with an average value of -365MPa, which is 17% higher than that of the AR-G sample. The high amplitude residual compressive stress on the surface of the LSPwC-G sample is a manifestation of the mechanical effect produced after the ablation layer on the surface of the LSPwC sample is removed by laser shock peening.
[0087] Typical low-magnification cross-sectional microstructure TEM images of LSPwC are shown in Figure 5 It can be seen that after LSPwC treatment, the depth of the heat affected zone reaches ~3.22 μm, and its cross-sectional microstructure contains nanocrystalline matrix and oxide particles Cr8O 21 This is related to the thermomechanical coupling effect induced by LSPwC. In the LSPwC process, as the surface material is completely vaporized, plasma and shock waves are formed. The high-pressure shock wave and the flowing water confinement layer cause the plasma to solidify rapidly again on the surface of the material. In this process, the mechanical effect of the laser shock wave causes severe plastic deformation of the martensitic stainless steel. At the same time, the thermal effect generated by the high temperature promotes the dynamic recrystallization process, which ultimately leads to the nano-crystallization of the matrix grains. In addition, the Cr element combines with the O element to form Cr8O 21 Oxide particles.
[0088] exist Figure 6 In (a), after removing the surface ablation layer, there is an obvious grain refinement layer near the sample surface due to the mechanical effect of the laser shock wave, and most of the grains show a nanoscale lath morphology. Below the refined grain layer is submicron Cr 15.58 Fe 7.42 C6, which indicates that the mechanical mixing of martensite and carbides during the laser shock wave-induced plastic deformation leads to the local dissolution of Cr-rich carbides. Figure 6 (b) shows the microstructure of the LSPwC-G sample at a depth of about 3 μm, which includes coarse martensite laths (about 460 nm in width) and nanoscale Cr on the lath boundaries. 15.58 Fe 7.42 C6 carbide.
[0089] The electrochemical impedance spectra of AR, AR-G, LSPwC and LSPwC-G measured in 3.5wt.% sodium chloride solution are shown in Figure 7As shown. The corrosion results show that the capacitance semicircle diameter of the LSPwC sample is much smaller than that of the AR sample, which indicates that the corrosion resistance of the LSPwC treatment is much worse. After removing all the ablation layers on the surface of the LSPwC sample, the LSPwC-G sample has a significantly increased capacitance semicircle diameter and the best corrosion resistance. In contrast, the AR-G sample obtained by grinding the AR sample has a significantly reduced capacitance semicircle diameter due to the rough surface caused by grinding, showing the lowest corrosion resistance. Figure 8 The electrochemical impedance spectrum of the sample of Example 2 measured in a 3.5wt.% sodium chloride solution. The results show that by increasing the laser power density by increasing the spot energy, reducing the spot diameter and increasing the spot overlap rate, the sample in Example 2 has a reduced capacitance semicircle diameter and reduced corrosion resistance relative to the LSPwC sample in Example 1. However, after removing the surface ablation layer, the sample in Example 2 has an increased capacitance semicircle diameter and increased corrosion resistance relative to the LSPwC-G sample in Example 1.
[0090] In contrast, Fig. 9 The electrochemical impedance spectrum of the sample of Example 3 measured in a 3.5wt.% sodium chloride solution. The results show that by reducing the laser power density by reducing the spot energy, increasing the spot diameter and reducing the spot overlap rate, the sample in Example 3 has an increased capacitance semicircle diameter and an increased corrosion resistance relative to the LSPwC sample in Example 1. After removing the surface ablation layer, the sample in Example 3 has a reduced capacitance semicircle diameter and a reduced corrosion resistance relative to the LSPwC-G sample in Example 1, but its corrosion resistance is still significantly increased compared to the LSPwC sample.
[0091] The passivation films on the surfaces of AR-G, LSPwC and LSPwC-G samples were analyzed using X-ray photoelectron spectroscopy. Fig.10 The results show that Cr 2P 3 / 2 The spectrum consists of metallic Cr, Cr oxides and hydroxides. Quantitative XPS analysis shows that the LSPwC sample is different from the other two samples in Cr 2P 3 / 2 There are obvious differences in the spectra. The Cr spectra of AR-G and LSPwC-G samples both show obvious metallic Cr spectra, while no metallic Cr spectra are detected in the Cr spectrum of the LSPwC sample. Among them, the intensity ratio of chromium oxide to chromium hydroxide in the AR-G sample is 1.28, 0.73 for the LSPwC sample, and 3.72 for the LSPwC-G sample.
[0092] After laser shock peening without protective layer, due to the large amount of Cr8O 21 The formation of the martensitic stainless steel surface coarsens, produces residual tensile stress, and forms a low Cr2O3 / chromium hydroxide ratio passivation film on the surface, which together lead to a sharp decrease in corrosion resistance (such as Fig.11 After removing the surface ablation layer, the smooth surface, residual compressive stress and high Cr2O3 / chromium hydroxide ratio passivation film produced by the decomposition of chromium-containing carbides significantly enhance the corrosion resistance of the material (as shown in Figure 2). Fig.11 (as shown in (b)).
[0093] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for improving the corrosion resistance of martensitic steel by laser shock hardening combined with polishing without protective layer, characterized in that: The following steps are involved: Grinding pretreatment of martensitic steel; The pretreated martensitic steel is subjected to a non-protective layer laser shock peening treatment, and during the non-protective layer laser shock peening treatment, running water is sprayed on the surface of the martensitic steel throughout the process; The martensitic steel after laser shock peening without protective layer is ground until the black ablation layer is completely removed.
2. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 1, characterized in that: The grinding pretreatment steps are: firstly grinding the surface of the martensitic steel to be processed with sandpaper, and then ultrasonically cleaning with anhydrous ethanol.
3. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 2, characterized in that: The step of first grinding the surface of the martensitic steel to be processed with sandpaper is: using 180-1500# SiC sandpaper to grind the surface of the martensitic steel to be processed step by step.
4. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 2, characterized in that: The ultrasonic cleaning time using anhydrous ethanol is 12-18 minutes.
5. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 4, characterized in that: The ultrasonic cleaning time using anhydrous ethanol was 15 min.
6. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 1, characterized in that: When the unprotected layer laser shock peening treatment is performed, the spot energy is 3-15J, the spot diameter is 1-6mm, the spot overlap rate is 30-70%, the spot pulse width is 16-20ns, the laser wavelength is 1064nm, and the frequency is 2Hz.
7. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 6, characterized in that: When the unprotected layer laser shock peening treatment is performed, the spot energy is 5-15J, the spot diameter is 1-3mm, the spot overlap rate is 30-60%, the spot pulse width is 16-18ns, the laser wavelength is 1064nm, and the frequency is 2Hz.
8. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 7, characterized in that: When the unprotected layer laser shock peening treatment is performed, the spot energy is 10 J, the spot diameter is 1 mm, the spot overlap rate is 60%, the spot pulse width is 18 ns, the laser wavelength is 1064 nm, and the frequency is 2 Hz.
9. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 1, characterized in that: The steps of grinding the martensitic steel after laser shock strengthening without a protective layer are as follows: grinding the black ablation layer with a scouring pad and abrasive paste in sequence until the black ablation layer is completely removed.
10. The method for improving the corrosion resistance of martensitic steel by laser shock peening combined with grinding without protective layer according to claim 9, characterized in that: The scouring pad is a 7447C scouring pad, and the abrasive paste is one of W2.5-W28 diamond abrasive pastes.
Citation Information
Patent Citations
Combination method for forming gradient nanostructure on surface layer of metal workpiece
CN107253148A
Combined treatment method for improving corrosion resistance of metal component in chloride-contained solution
CN107385193A
Surface strengthening device and method combining laser shock peening and mechanical polishing
CN113579969A
Coating-free laser shock peening method for surface of blade of plastic granulator
CN117778701A
Anti-corrosion method for thermal composite laser shock peening magnesium alloy
CN117845046A